防己 추출물이 LPS로 유도된 Raw 264.7 cell에서의 TNF-α, IL-1β, IL-6 및 Nitric Oxide production에 미치는 영향 - 김대희(Dae Hee Kim); 이종록(Jong Rok Lee); 변성희(Sung Hui Byun); 신상우(Sang Woo Shin); 권영규(Young Kyu Kwon); 김상찬(Sang Chan Kim) (동의생리병리학회지, 2006)
Tetrandra is the root of Stephania tetrandra S. Moore (family Menispermaceae), or of Aristolochia frangchi Wu (family Aristolochiaceae). It is a bitter-flavored and cold-property herb acting on the urinary bladder, kidney and spleen meridiands. Known biological effects of this herb are expelling wind to relieve pain and inducing diuresis to alleviate edema. This herb also has anti-inflammatory and anti-hypersensitivity actions. Recent studies have shown that Stephanniae Tetrandrae Radix has antimicrobial effects, namely, a protective effect on acute renal failure induce by gentamicin sulfate and a suppressive effect against clostridium perfringes. However, there is a lack of studies concerning the immunological activities of this herb. The present study was conducted to evaluate the immunological activities of Stephanniae Tetrandrae Radix on the regulatory mechanisms of cytokines and nitric oxide (NO) in Raw 264.7 cells. Cell viability was measured by MTT assay after the treatment of Stephanniae Tetrandrae Radix extract (STRE) and NO production was monitored by measuring the nitrite content in culture medium. COX-2 and iNOS were determined by immunoblot analysis, and levels of cytokine were analyzed by sandwich immunoassays. Results provided evidences that STRE inhibited the production of nitrite and nitrate (NO), inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2) tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) in Raw 264.7 cells activated with lipopolysaccharide (LPS). These findings showed that STRE could produce some anti-inflammatory effects which might play a role in adjunctive therapy in Gram-negative bacterial infections. KCI Citation Count: 1